Legal Pluralism, Epistemic Tensions, and the Reformulation of the Adultery Offense in Indonesia’s New Penal Code - Mubayyinah, Fira; Handayani, Febri; Sifa’, Moh. Agus (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2025)
This article examines the reformulation of the adultery offense in Indonesia’s new Penal Code (Law No. 1 of 2023) through a socio-legal approach informed by postcolonial analytical frameworks. Focusing on the adultery provision as a representative case, the study investigates how moral, religious, and customary arguments were articulated, contested, and negotiated by actors involved in the legislative process. Employing thematic content analysis of the old and new Penal Codes, the Academic Draft, and parliamentary deliberation transcripts, the findings reveal that although the new Penal Code expands the substantive definition of adultery to encompass all sexual relations outside of marriage, it simultaneously retains procedural structures and evidentiary rules inherited from the colonial legal tradition. This dynamic generates significant epistemic tension: while local normative values—particularly those derived from Islamic and customary traditions—are invoked as sources of moral legitimacy, their incorporation remains constrained by a positivist legal framework shaped by colonial legacies. The resulting legal framework reflects a partial and uneven transformation that does not fundamentally alter the epistemic foundations of Indonesia’s criminal law. The article argues that substantive decolonization necessitates not only the inclusion of locally grounded norms but also a critical engagement with the procedural and epistemic structures through which these norms are translated into national legislation.